STRATEGI MARKETING PUBLIC RELATIONS DIVISI MEDIA PLANNER DALAM MEMBANGUN BRAND AWARENESS PADA CHANNEL GTV PAY, MNCTV PAY, RCTI PAY DI MNC CHANNELS - Ginting, Korina Lolita; Guyub Nuryanto (Asosiasi Dosen Muda Indonesia, 2024)
This research aims to identify the public relations marketing strategies employed by the media planner division in building brand awareness at MNC Channels. In this study, the researcher uses a qualitative method with a descriptive approach and a constructivist paradigm. The informants in this study are employees of MNC Channels in the media planner division. In this research, the researcher employs the excellence theory. The result of this research is that MNC Channels has successfully implemented a public relations marketing strategy, particularly in building brand awareness aimed at increasing the recognition and presence of the brand, carried out by the media planner division. The public relations marketing strategy employed by the media planning division also encompasses the concept from Thomas L. Harris, which includes the three ways strategy: pull strategy, push strategy, and pass strategy.